Epidemiology of sickle cell disease in tribal population of Southern Rajasthan, India - Anil Purohit; Ramesh K. Huda; Suman S. Mohanty; Bontha V. Babu (Scientific Reports)
Abstract Background & objectives Sickle Cell Disease (SCD), a genetic condition, carries significant public health implications due to its impact on mortality, morbidity and quality of life. SCD is prevalent among tribal communities. The objective of this study was to conduct a screening of the tribal population and report the prevalence of SCD in southern Rajasthan, India. Methods A cross-sectional study was conducted in two blocks of southern Rajasthan to determine the prevalence of Sickle Cell Trait (SCT) and SCD. The study population underwent screening for SCD initially using the solubility test method. Family members of individuals tested positive for the solubility test were also screened. Subsequently, blood samples were collected from individuals who were positive for the solubility test. The confirmation of SCT and SCD was carried out through HPLC. Results The prevalence of SCT and SCD was 9.87% and 0.32%, respectively. The highest combined prevalence (including SCT and SCD) of 15.52% was observed among the Garasiya tribe, followed by the Bhil tribe with the prevalence of 9.68%. Conclusion SCD is moderately prevalent, with less than a per cent among the tribal population of Southern Rajasthan. However, the prevalence of SCT is about 10%. The study also highlights the feasibility of implementing a population-based screening program. This program can be readily implemented within tribal habitations as a component of the proposed national SCD program.